Game Plan : A Geostrategic Framework for the Conduct of the U.S.--Soviet Contest - Brzezinski, Zbigniew (Rawalpindi Army Education Press, 1986)
"Game Plan" is not an argument about the evils of the Soviet empire or the attractions of American democracy, but a guide to action. The author stresses that the United States must seek to manage the conflict over the long term so that it prevails historically. That, he points out, requires a geopolitical strategy and a clear set of priorities.
Include Maps, Appendix and Index.
Keywords: United States -- Soviet Union -- Strategic aspects of individual places -- Diplomatic relations -- Geopolitics